Sex Effects on Managerial Hiring Decisions - Rose, Gerald L.; Andiappan, P. (Academy of Management Journal, 1978)
Subjects evaluated hypothetical male and female applicants for managerial positions. Half required supervision of predominately female subordinates; half the supervision of predominately male subordinates. Females expected higher performance than males. Males and females favored applicants whose sex matched the subordinates'. Thus, the sex-role context, not merely the applicant's sex, may induce selection discrimination.